272 Digital Breast Tomosynthesis Index (DBTI): A score to evaluate Digital Breast Tomosynthesis (DBT) device. (December 2018) - Loria, A.; Signorotto, P.; Venturini, E.; Panizza, P.; del Vecchio, A.
Abstract : Purpose: The aim of this study is to combine image quality (IQ) and dosimetric parameters into a score to evaluate the goodness of a digital breast tomosynthesis (DBT) device. Methods: Digital Breast Tomosynthesis Index (DBTI) is derived from two figure of merit (FoM) introduced to evaluate CT devices (Rose and ImPACT)[1] . These FoMs include parameters as contrast-to-noise ratio (CNR), spatial resolution in terms of modulation transfer function (MTF), slice thickness and a dosimetric quantity (CTDI). In the same way, DBTI is designed to have a quadratic dependence from signal-difference-to-noise ratio (SDNR), cubical dependence from the MTF, and to be inversely proportional to slice-sensitivity profile (SSP) and average glandular dose (AGD). IQ parameters were measured using the Tomophan phantom. SDNR was evaluated with the 0.2 mm thick aluminum insert. MTF was calculated for scan and sub-scan directions from the point spread function of the 0.18 mm tungsten bead. SSP evaluation was performed with the two reversing angled bead ramps method. These parameters were evaluated for two different DBT devices at seven different values of AGD, obtained manually setting the tube current time product. Results: Each DBT device showed a characteristic value of DBTI. These values were constant as the tube current time product changes, with a standard deviation of 2% and 6% for the two devices. Conclusions: Independence of DBTI from exposure parameters could make it a good FoM to benchmark DBT devices. Compared to CT, DBT have less clinical questions, so a single score could provide a reliable estimation of the goodness of the DBT device.